Respuesta :
Hello!
The answer is:
The equation of the given circle is:
[tex](x-4)^{2}+(y+5)^{2}=13[/tex]
Why?
The equation of a circle is given by the following equation:
[tex](x-h)^{2} +(y-k)^{2}=r^{2}[/tex]
We are given the center point (4,-5) and the radius.
So,
Where:
[tex]h=x=4\\k=y=-5\\r=\sqrt{13}[/tex]
Then, substituting into the circle equation, we have:
[tex](x-4)^{2} +(y-(-5))^{2}=(\sqrt{13})^{2}[/tex]
[tex](x-4)^{2} +(y-(-5))^{2}=(\sqrt{13})^{2}[/tex]
Hence, the simplified equation of the circle is:
[tex](x-4)^{2}+(y+5)^{2}=13[/tex]
Have a nice day!
Answer:
The required equation in standard form is [tex](x-4)^2+(y+5)^2=13[/tex]
Step-by-step explanation:
The equation of a circle with center (h,k) an radius, r units is given by the formula;
[tex](x-h)^2+(y-k)^2=r^2[/tex]
The given circle has center (4,-5) and radius [tex]r=\sqrt{13}[/tex].
We substitute these values into the formula to obtain;
[tex](x-4)^2+(y--5)^2=(\sqrt{13})^2[/tex]
We simplify to get;
[tex](x-4)^2+(y+5)^2=13[/tex]